Preparation and physicochemical characterization of a diclofenac sodium-dual layer polyvinyl alcohol patch - Saadon S.; Ansari M.N.M.; Razak S.I.A.; Anand J.S.; Nayan N.H.M.; Ismail A.E.; Khan M.U.A.; Haider A. (MDPI AG, 2023)
Contact angle; Crystallinity; Fourier transform infrared spectroscopy; Freezing; Gelation; Nanofibers; Physicochemical properties; Polyvinyl alcohols; Scanning electron microscopy; Sodium; Tensile strength; Tensile testing; Thawing; X ray diffraction; Electrospinning techniques; Fourier transform infrared; Freeze-thaw process; Morphological structures; Physico-chemical and mechanical properties; Physico-chemical characterization; Spectroscopic technique; Transdermal drug delivery; Drug delivery